COVID-19 AND THE PERCEPTION OF STUDENTS OF A HIGHER EDUCATION INSTITUTION IN THE EXTREME SOUTH OF BAHIA - Martins Ribeiro, Alessandro; Nunes Rey, Pedro; Gabriel Lucas Macedo, Igor; Miranda Lago, Vivian (Journal of Interdisciplinary Debates, 2021)
Introduction: The current pandemic experienced in Brazil and worldwide has caused numerous problems in all sectors of the economy, interfering directly in the educational area, from pre-school to higher education, it is well known that without students, there will be no educational institution and this class has been very affected since the beginning of the infection by COVID-19. Methodology: A cross-sectional study of the opinion survey type was carried out; the sample consisted of university students from a private college in the southernmost part of Bahia, where all participants agreed to answer the questionnaire. Results and Discussions: a total of 128 students were interviewed, 28.90% identified themselves as male, 70.31% identified themselves as female and 0.79% identified themselves as other.  It was possible through this study to realize the negative impacts of social isolation arising from the COVID-19 pandemic that has been established in the year 2020.